Carolina Cradle : Settlement of the Northwest Carolina Frontier, 1747-1762 - Ramsey, Robert Wayne (Book collections on Project MUSE., 1987)
Describes the "invasion" of emigrant families into the area and their socio-economic and religious reasons for migrating during the period. A #87-442 Gift-Friends of the Genealogy Collection